2022
DOI: 10.1128/spectrum.01829-22
|View full text |Cite
|
Sign up to set email alerts
|

3-Phenylpropan-1-Amine Enhanced Susceptibility of Serratia marcescens to Ofloxacin by Occluding Quorum Sensing

Abstract: Multidrug-resistant bacteria have become a major threat to global public health, leading to increased morbidity, mortality, and health care costs. Bacterial virulence factors and biofilms, which are regulated by quorum sensing (QS), are the primary causes of multidrug resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“… 40 Past studies reported that S. marcescens enhanced its infectivity and its inherent resistance to antibiotics through plasmids and efflux pumps, which greatly contributed to the emergence of multiple drug-resistant strains and finally complicated the treatment process, 41 , 42 and the underlying mechanisms were complicated. 43 In our study, regardless of the two S. marcescens isolates resistant to cefazolin, meropenem, and chloramphenicol simultaneously, the efflux pump-related genes sdeB, sdeD, sdeR, sdeS , s deY , or hasF (in combination) were observed in all β-lactams and chloramphenicol-resistant isolates, respectively. Efflux pump is helpful for bacteria to excrete antibiotics, and it is the main cause of clinical intrinsic and acquired multidrug resistance in bacteria.…”
Section: Discussionmentioning
confidence: 45%
“… 40 Past studies reported that S. marcescens enhanced its infectivity and its inherent resistance to antibiotics through plasmids and efflux pumps, which greatly contributed to the emergence of multiple drug-resistant strains and finally complicated the treatment process, 41 , 42 and the underlying mechanisms were complicated. 43 In our study, regardless of the two S. marcescens isolates resistant to cefazolin, meropenem, and chloramphenicol simultaneously, the efflux pump-related genes sdeB, sdeD, sdeR, sdeS , s deY , or hasF (in combination) were observed in all β-lactams and chloramphenicol-resistant isolates, respectively. Efflux pump is helpful for bacteria to excrete antibiotics, and it is the main cause of clinical intrinsic and acquired multidrug resistance in bacteria.…”
Section: Discussionmentioning
confidence: 45%
“…Swimming mediated by flagella was decreased by 53% at 400 μg/mL. In a previous study, 3-phenylpropan-1-amine (3-PPA) was found to inhibit S. marcescens NJ01 biofilm formation and virulence factors, such as prodigiosin, protease, lipase, hemolysin, and swimming motility [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…S. marcescens NJ01 forms biofilms through a series of defined stages that culminate in a highly porous, filamentous biofilm composed of cell chains, filaments, and cell clusters dependent on the quorum-sensing systems [ 13 , 39 , 40 ]. Bacteria susceptible to antimicrobial agents can become resistant after forming a biofilm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenylpropane-1-amine (3-PPA) is known to be an antibiotic adjuvant that interferes with QS and disrupts signaling between bacteria without posing a threat to the bacteria themselves, potentially resolving resistance in pathogenic bacteria [6]. In this recent and unique study, 3-phenylpropan-1-amine (3-PPA) was determined to inhibit biofilm formation.…”
Section: Anti-biofilm Activity Of Peptides and Organic Compounds 21 A...mentioning
confidence: 99%